A educação profissional tecnológica como ação pública promotora da formação humana integral e da inclusão de jovens em risco social no mundo do trabalho - Silva, José Barbosa da (2020)
This research was developed during the Professional Master in Professional and Technological Education - ProfEPT whose theme deals with Professional Technological Education as a public action that promotes integral human formation and the inclusion of young people at social risk in the world of work, with the main focus of the research the professional carpentry course, promoted by the José Cornélio Professional Training Project, carried out by the Municipal Social Development Secretariat, SEMDES, in the Municipality of Óbidos, State of Pará. In this sense, the general objective of the research is to analyze the conceptions of work and professional training present in that course and its contribution to the process of social inclusion of young people at social risk in the world of work and in preparing for life. The research methodology followed the methodological assumptions of a case study in a qualitative perspective, which includes the development of bibliographic research and field research. Concerning bibliographic research, a survey of works and authors dealing with the topic was carried out. In field research, data collection techniques were participant observation, open and semi-open interviews and document analysis. As a data collection instrument, structured and semi-structured questionnaires and conversation circles were used, which were recorded. The research followed the philosophical approach of materialism-historical-dialectic, because this conception of the world clearly explains the material reality and the contradictions that exist in the intricacies of the social relations of production and the construction of human existence. The research results point to the existence in the carpentry course and in the other activities of the José Cornélio Training Project of the conceptions of work and professional training linked to the idea of work as the creation and production of human existence. In addition, the educational practices that reward the daily life of the PJFC contribute significantly to the integral formation of young people and their inclusion in the world of work, while highlighting elements that serve as obstacles to an emancipatory formation and that are consistent with the restricted conception of work as a synonym for employability. Thus, the production of the Educational Application José Cornélio was presented as a final product, a didactic tool that contains pedagogical strategies that intends to contribute to the process of integral human formation of the future carpenter (a) trained in the José Cornélio Formation Project.